THE ROLES OF THE QUADRICEPSPLASTY IN TREATMENTS OF POST- TRAUMATIC STIFF KNEE (USING JUDET PROCEDURE) - Muwafaq Siham Mahdi; Abdulrazzaq Salim Mahdi (Scholar Express Journals, 2023)
The lack of knee flexion is an increasingly recognized complication especially after trauma. This is a significant challenge for both surgeon and patients. In 1956, Judet proposed a quadricepsplasty technique that allowed for a graded release without the disruption of the vastus medialis, vastus lateralis, or rectus femoris
Keywords: knee joint; quadricepsplasty; post-traumatic stiffness